2015
DOI: 10.1002/ffj.3246
|View full text |Cite
|
Sign up to set email alerts
|

In‐depth analysis of Ciflorette strawberries (Fragaria × ananassa ‘Ciflorette’) by multidimensional gas chromatography and gas chromatography‐olfactometry

Abstract: Grown predominantly in France, Ciflorette strawberries (Fragaria × ananassa ‘Ciflorette’) possess a well‐balanced fruity aroma and a sweet, creamy taste. The goal of this study was to better understand the chemical composition and key odourants of this unique fruit. Incorporating fractionation and multidimensional gas chromatography‐mass spectrometry (MDGC‐MS), the volatile constituents of Ciflorette strawberries are discussed for the first time from the large‐scale extraction of 100 kg of the pureed berries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 37 publications
(43 reference statements)
4
34
1
Order By: Relevance
“…8 More and more compounds containing this olfactophore have been reported to occur in nature [9][10][11][12] and many have been approved as safe flavour ingredients by the Flavour and Extract Manufacturers' Association (FEMA). 13 The homologues of 3-methylthioalkanals, which contain a 1,3-oxygen-sulfur functionality occur widely as volatile aroma components of various plants, [14][15][16][17] fruit, 18 vegetables, 19 and cooked beef liver 20 and seafoods. 21 3-Methylthiodecanal is a relatively new flavour compound, which was added to the GRAS (Generally Recognized as Safe) list in 2013.…”
mentioning
confidence: 99%
“…8 More and more compounds containing this olfactophore have been reported to occur in nature [9][10][11][12] and many have been approved as safe flavour ingredients by the Flavour and Extract Manufacturers' Association (FEMA). 13 The homologues of 3-methylthioalkanals, which contain a 1,3-oxygen-sulfur functionality occur widely as volatile aroma components of various plants, [14][15][16][17] fruit, 18 vegetables, 19 and cooked beef liver 20 and seafoods. 21 3-Methylthiodecanal is a relatively new flavour compound, which was added to the GRAS (Generally Recognized as Safe) list in 2013.…”
mentioning
confidence: 99%
“…Berry fruits are another important class with particular properties. Their aroma and flavour were the focus of various MDGC studies, including strawberries [30,31], raspberries [32], blue honeysuckle, chokeberry, bilberry [33]. Samykanno et al [30], applied GC×GC-TOFMS to obtain the volatile profiles of two varieties of strawberries harvested in Australia (Albion and Juliette).…”
Section: Foodmentioning
confidence: 99%
“…They identified a total of 94 volatiles of which 20 were not previously reported in the literature. Cannon et al [31] also analysed strawberry samples of Ciflorette variety, using a MDGC-MS system. According to the authors, the methodology allowed the identification of 252 compounds not previously reported in strawberries.…”
Section: Foodmentioning
confidence: 99%
“…Butenolides have been reported to occur widely in nature as volatile components of many foods, such as fruits, vegetables, drinks, edible oils, and meat products, since they were first identified in deep‐frying corn oil early in 1967 . They were described to present diverse odour features: fatty, grassy, sweet, fruity, coconut‐like, mushroom, and caramel .…”
Section: Introductionmentioning
confidence: 99%